Respuesta :

Answer:

[tex]\left \{ {{y=-1} \atop {x=-4}} \right.[/tex]

Step-by-step explanation:

[tex]\left \{ {{y=\frac{3}{4} x+2} \atop {5x+4y=-24}} \right. <=> \left \{ {{y=\frac{3}{4}x+2 } \atop {5x+4*(\frac{3}{4}x+2)=-24 }} \right. <=>\left \{ {{y=\frac{3}{4}x+2 } \atop {5x+3x+8=-24}} \right. <=> \left \{ {{y=\frac{3}{4}x+2 } \atop {8x=-32}} \right. \\<=>\left \{ {{y=\frac{3}{4}x+2 } \atop {x=-4}} \right. <=> \left \{ {{y=\frac{3}{4}*(-4)+2 } \atop {x=-4}} \right. <=> \left \{ {{y=-3+2} \atop {x=-4}} \right. =>\left \{ {{y=-1} \atop {x=-4}} \right.[/tex]